Walk Score and Australian adults' home-based walking for transport. (September 2015) - Cole, Rachel; Dunn, Peter; Hunter, Ian; Owen, Neville; Sugiyama, Takemi
Abstract: The relationships of Walk Score, a publicly-accessible walkability assessment tool, with walking for transport to and from home were examined among a large representative sample of Australian adults aged 18–64 years ( N =16, 944). Residents in highly and somewhat walkable areas were twice and 1.4 times more likely to accumulate 30 min of walking per day compared to those in very car-dependent neighborhoods, respectively. Mean duration of walking was also longer for participants living in highly and somewhat walkable areas compared to those in very car-dependent areas. Walk Score has potential as a widely-applicable tool for identifying the walkability of local neighborhoods. Highlights: Walk Score is a measure of neighborhood walkability based on the access to local destinations. Residents in higher walkable areas were more likely to walk for 30 min per day. Mean walking duration was longer for those living in high walkable areas than in low walkable areas. Walk Score may be a broadly-applicable user-friendly tool to identify neighborhood walkability.